1995
DOI: 10.3928/0098-9134-19951001-06
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Bran Supplement on the BOWEL MANAGEMENT OF ELDERLY REHABILITATION PATIENTS

Abstract: 1. Constipation is a common problem in the elderly that affects up to 20% of those 65 years and older. 2. Patients receiving the fiber supplement had a significantly lower number of bowel agents per day as compared to the control patients. 3. Side effects from the additional fiber occurred in a subgroup of patients; thus, institution of additional fiber to the diets of ill, physically dependent patients is best done gradually and with close monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…To ensure that the desirable daily fluid intake is achieved to prevent constipation, 10 or more cups/glasses would need to be consumed, therefore this was scored 'zero'. A fluid intake of a minimum of 1.5 l/day was considered adequate for constipation prevention (Meza et al, 1984;Rodrigues-Fisher et al, 1993;Gibson et al, 1995;Armstrong-Esther et al, 1996;Ouellet et al, 1996;Duffy and Zernike, 1997) and would measure at 6 cups/glasses per day (Wilson, 1999). The sub-category of '6-9 cups/glasses consumed daily' was then included, which was scored as 'one'.…”
Section: Fluid Intakementioning
confidence: 99%
“…To ensure that the desirable daily fluid intake is achieved to prevent constipation, 10 or more cups/glasses would need to be consumed, therefore this was scored 'zero'. A fluid intake of a minimum of 1.5 l/day was considered adequate for constipation prevention (Meza et al, 1984;Rodrigues-Fisher et al, 1993;Gibson et al, 1995;Armstrong-Esther et al, 1996;Ouellet et al, 1996;Duffy and Zernike, 1997) and would measure at 6 cups/glasses per day (Wilson, 1999). The sub-category of '6-9 cups/glasses consumed daily' was then included, which was scored as 'one'.…”
Section: Fluid Intakementioning
confidence: 99%
“…Research examining risk factors in an elderly population (n = 36) concluded that fibre and fluid intake was not significantly different in constipated versus non-constipated individuals (Towers et al, 1994). Values provided for fluid intake in the two groups indicate that ''3.4 glasses (8 oz) of fluid'' were consumed on average daily, which is lower than the recommended minimum fluid intake (Alford, 1991;Rodrigues-Fisher et al, 1993;Gibson et al, 1995). Values provided for fluid intake in the two groups indicate that ''3.4 glasses (8 oz) of fluid'' were consumed on average daily, which is lower than the recommended minimum fluid intake (Alford, 1991;Rodrigues-Fisher et al, 1993;Gibson et al, 1995).…”
Section: Role Of Fluid Intakementioning
confidence: 91%
“…Research among healthy subjects also revealed that increased fluid intake had no effect on stool output (Ziegenhagen et al, 1991;Gibson et al, 1995;Chung et al, 1999). In Chung et al's study (1999) healthy volunteers (aged 23-46 years) (n = 15) consumed isotonic fluids (1 liter) or free fluids (>2 litres) over their baseline for a period of two days with no difference in bowel function between the two groups.…”
Section: Role Of Fluid Intakementioning
confidence: 97%
See 1 more Smart Citation
“…Constipation and diarrhoea are often considered common among older people ( Gibson et al . 1995 ; Neal, 1995) yet there is little research addressing these, and the related problems of excessive flatus and laxative use.…”
Section: Literature Reviewmentioning
confidence: 99%